The Philippines has mainstreamed the climate risk vulnerability assessment framework, through the integrated CRVA-PCIP protocol in upgrading existing provincial commodity investment plans - Palao Kris, Leo M (2022)
In 2020, the Climate Risk Vulnerability Assessment (CRVA) framework, developed by CCAFS/Alliance, gained recognition as a vital tool in combating the escalating climate pressures on the Philippines' agricultural sector. The Department of Agriculture (DA) adopted the CRVA as a standardized and evidence-based assessment tool. It establishes 54 AMIA villages and guides Provincial Commodity Investment Plans (PCIPs) to address climate impacts on agriculture. CRVA aids in identifying and prioritizing vulnerable crops at municipal levels. DA's 2021 memorandum mandates CRVA results' use to enhance PCIPs, crucial for local economic development. The tool helps stakeholders comprehend risks, select resilient crops, and adapt to changing climates. One of the strengths of the CRVA lies in its localized analyses, ensuring accuracy and reliability. This bottom-up approach not only enhances the precision of vulnerability assessments but also fosters a sense of ownership among local communities, spurring them to actively participate in adaptive strategies.